2014
DOI: 10.1373/clinchem.2013.220376
|View full text |Cite
|
Sign up to set email alerts
|

Measurements for 8 Common Analytes in Native Sera Identify Inadequate Standardization among 6 Routine Laboratory Assays

Abstract: BACKGROUND External quality assessment (EQA) with commutable samples is essential for assessing the quality of assays performed by laboratories, particularly when the emphasis is on their standardization status and interchangeability of results. METHODS We used a panel of 20 fresh-frozen single-donation serum samples to assess assays for the measurement of creatinine, glucose, phosphate, uric acid, total cholesterol, HDL cholesterol, LDL cholesterol, and triglycerides. The commercial random access platforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…For many analytes, our findings were comparable, e.g. glucose and cholesterol met, quality criteria whereas HDL cholesterol (Abbott) did not [8], neither did calcium and total protein meet the criteria [6]. We found that alkaline phosphatase (AP), alanine aminotransferase (ALAT), aspartate aminotransferase (ASAT), and lactate dehydrogenase (LD) were not traceable to the respective IFCC RMPs.…”
Section: Comparison With Similar Eqa Conceptsmentioning
confidence: 62%
See 3 more Smart Citations
“…For many analytes, our findings were comparable, e.g. glucose and cholesterol met, quality criteria whereas HDL cholesterol (Abbott) did not [8], neither did calcium and total protein meet the criteria [6]. We found that alkaline phosphatase (AP), alanine aminotransferase (ALAT), aspartate aminotransferase (ASAT), and lactate dehydrogenase (LD) were not traceable to the respective IFCC RMPs.…”
Section: Comparison With Similar Eqa Conceptsmentioning
confidence: 62%
“…It is possible that other contrasting findings, e.g. uric acid and Mg (Abbott) had a similar cause [6].…”
Section: Comparison With Similar Eqa Conceptsmentioning
confidence: 98%
See 2 more Smart Citations
“…The focus of the master comparisons, which are conducted across assays and laboratories, is on how well the intrinsic analytical quality of assays released by the respective manufacturers is reproduced by the end users under "field" conditions all over the world. Results about master comparison with a panel of 20 frozen single donation samples for calcium, magnesium, albumin, total protein [16,17], sodium [18], creatinine, glucose, phosphate, uric acid, total cholesterol, HDL cholesterol, LDL cholesterol and triglycerides [19], have been previously described. In a recent survey AST, ALT, LDH, GGT and ALP, sodium, potassium and chloride have been added.…”
mentioning
confidence: 99%